Fluoride Leaching of Titanium from Ti-Bearing Electric Furnace Slag in [NH4+]-[F−] Solution - Fuqiang Zheng; Yufeng Guo; Feng Chen; Shuai Wang; Jinlai Zhang; Lingzhi Yang; Guanzhou Qiu (Metals, 2021)
The effects of F− concentration, leaching temperature, and time on the Ti leaching from Ti-bearing electric furnace slag (TEFS) by [NH4+]-[F−] solution leaching process was investigated to reveal the leaching mechanism and kinetics of titanium. The results indicated that the Ti leaching rate obviously increased with the increase of leaching temperature and F− concentration. The kinetic equation of Ti leaching was obtained, and the activation energy was 52.30 kJ/mol. The fitting results of kinetic equations and calculated values of activation energy both indicated that the leaching rate of TEFS was controlled by surface chemical reaction. The semi-empirical kinetics equation was consistent with the real experimental results, with a correlation coefficient (R2) of 0.996. The Ti leaching rate reached 92.83% after leaching at 90 °C for 20 min with F− concentration of 14 mol/L and [NH4+]/[F−] ratio of 0.4. The leaching rates of Si, Fe, V, Mn, and Cr were 94.03%, 7.24%, 5.36%, 4.54%, and 1.73%, respectively. The Ca, Mg, and Al elements were converted to (NH4)3AlF6 and CaMg2Al2F12 in the residue, which can transform into stable oxides and fluorides after pyro-hydrolyzing and calcinating.